Analysis of Demotivation Factors in Learning English of Senior High School Students - Annisrina Fajri Nugraheni; Arda Mageso Ismariyanto; Lilia Indriani (Faculty of Education and Teachers Training, 2021)
Learners' motivation has long been recognized as a critical element influencing the rate, success, and failure of second/foreign language learning. On the other hand, demotivation is considered the inverse of motivation and has a detrimental impact on language learning processes and outcomes. This study aims to determine the most influential cause of demotivation in adolescents aged 16-18 years learning English. It also studied the frequency and order of relevance of the demotivating variables to determine which aspects are the most significant and their relationships to the learners' gender and degree of education. The subjects used in this study were high school students who, on average, had the same background.